ENGLISH TEACHING IMPLEMENTATION IN INDONESIAN PESANTRENS: TEACHERS’ DEMOTIVATION FACTORS - Habibi, Akhmad; Sofwan, Muhammad (IJET (Indonesian Journal of English Teaching), 2016)
This qualitative inquiry is aimed at analysing demotivation factors of teachers in Indonesian Pesantrens (Islamic Boarding School) in implementing EFL teaching. The research is appropriately undertaken as a qualitative research with a case study approach. The research sites for this study are two Pesantrens in Jambi, one of Indonesian Provinces. Eight English teachers were involved as the participants to providebroader perspectives of the participants in relation to the EFL teaching. The researcher use three kinds of instruments in collecting the data; interview, focus group discussion, and document review. The researcher conducted the observation, interviewed the teachers, held focus group discussion, and collected related documents to support the data.To assess the trustworthiness of the research, the researcher did triangulation, member checking and reflexivity. The findings describe working condition (financial matter and working overload); curriculum (rapid changing of Indonesian curriculum and lack of teaching and supporting materials); facilities (classroom temperature and over-crowded classroom); students (lack of basic knowledge and lack of motivation).